Band gap formation and Anderson localization in disordered photonic materials with structural correlations - Froufe-Perez, Luis S.; Engel, Michael; Jose Saenz, Juan; Scheffold, Frank (Proceedings of the National Academy of Sciences of the United States of America, 2017)
Disordered dielectric materials with structural correlations show unconventional optical behavior: They can be transparent to long-wavelength radiation, while at the same time have isotropic band gaps in another frequency range. This phenomenon raises fundamental questions concerning photon transport through disordered media. While optical transparency in these materials is robust against recurrent multiple scattering, little is known about other transport regimes like diffusive multiple scattering or Anderson localization. Here, we investigate band gaps, and we report Anderson localization in 2D disordered dielectric structures using numerical simulations of the density of states and optical transport statistics. The disordered structures are designed with different levels of positional correlation encoded by the degree of stealthiness extgreekq. To establish a unified view, we propose a correlation-frequency ( extgreekq– extgreekn) transport phase diagram. Our results show that, depending only on extgreekq, a dielectric material can transition from localization behavior to a band gap crossing an intermediate regime dominated by tunneling between weakly coupled states.
EAM Import::2019-03-13